The Hellenistic Poleis of Southern Babylonia and the Erythraean Sea - Neugebauer, Gillian Ramsey (Anabasis. Studia Classica et Orientalia, 2022)
Greek inscriptions, Babylonian cuneiform tablets, archaeology, and assorted literary passages attest to a network of Hellenistic colonial cities in southern Mesopotamia and around the Persian Gulf. Through this evidence we get glimpses of the histories and famous scions of these far-flung Greek poleis, and their connections to each other and the wider world. This paper will consider what we can know about Antiocheia in Persis, Seleukeia on the Erythraean Sea, and their neighbours – caught up in the political changes when the Parthians conquered Babylonia and the kingdom of Mesene/Charakene emerged. Comparison of their geographical situations allows postulation of a regional riverine and overland trade system, comparable to other significant zones of Hellenistic colonization in Syria and Kilikia. But most evident in the diverse evidence is how these communities engaged with the cultural and intellectual networks spanning the Hellenistic world, ranging from participation in the traditional religious and athletic festival for Artemis Leukophryene at Magnesia in “Old Greece”, to Seleukos of Selekeia alias Seleukos of Babylon’s exchanges of mathematical proofs and astronomical theories with the philosophers of Alexandreia and beyond.